Drivers’ experiences during floods: Investigating the psychological influences underpinning decisions to avoid driving through floodwater - Hamilton, K.; Price, S.; Keech, J.; Peden, A.; Hagger, Martin (Elsevier BV, 2018)
A major risk factor for many flood-related drownings is driving through floodwater. We aimed to understand Australian drivers’ experiences and beliefs with respect to avoid driving through floodwater using the theory of planned behaviour as a framework. Study 1 (N = 23) used a qualitative design to gain an in-depth understanding of individuals’ experiences with driving through floodwater. Study 2 (N = 157) used a survey-based design to identify the factors related to this behaviour including knowledge, beliefs, and social-cognitive factors. In Study 1, drivers identified a range of advantages (e.g., didn't damage car), disadvantages (e.g., inconvenient, but not so terrible), barriers (e.g., urgency to reach destination), and facilitators (e.g., making plans and using existing plans) to avoiding driving through floodwater. Normative factors were also important influences on drivers’ decisions including normative expectancy, approval of significant others, and a moral obligation for the safety of others. In Study 2, participants were able to recall information about driving through floodwater (e.g., dangerous/risky) and its meaning (e.g., body of water over road). A range of experiences were described for avoiding driving through floodwater (e.g., took an alternative route). Across the studies, a range of behavioural, normative, and control beliefs were elicited. Finally, sex (women more likely), attitude, subjective norm, and perceived behavioural control significantly predicted intentions to avoid driving through floodwater, with the model explaining 55% of the variance. These findings can inform intervention targets and development of prevention strategies for effective behaviour change, saving lives otherwise lost to Australian waterways in flood.